The Cairo Trilogy: An Existential Reading in Three Generations of this Novel - Ali Dakhil Naem; Lajiman Bin Janoory (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The researcher in this paper elaborates the writings of Naguib Mahfouz from an existential perspective in Cairo Trilogy. Mahfouz concludes that western scholars and politicians conceal the realities of daily life in Egypt, which Mahfouz reveals. In Mahfouz’s Cairo Trilogy, one can find an openness and acceptance in Egyptian society for other faiths and cultures. The researcher will illustrate how there is an important acceptance of internal existential and religious struggles amongst individuals in the society during this novel. The researcher focuses on the character and the inner psychological conflicts in these characters. It seems that this is an important aspect of Egyptian identity. The idea that Egyptians or Muslims are struggling mainly with the West is contradictory to Mahfouz’s characterizations. He asserts that Egyptians have their own internal struggles because of the diversity of their ideologies.